ANALISIS PERAN STAKEHOLDERS DALAM PENGELOLAAN RUANG TERBUKA HIJAU DI HUTAN KOTA BEKASI - Febrian Putra, Jagad; Djumiarti, Titik; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2024)
This research aims to examine the roles of stakeholdersiinitheimanagementiof green openispacesiin the Bekasi City Forest. Effective management requires cooperation and participation from various stakeholders with diverse interests and roles. Data collectioniwasiconductedithroughidocumentationistudies, interviews, and observations. Theiinformant selectionitechnique used purposiveisampling to select informants providing primary and secondary data. Informants included the Environmental Agency, the Department of Public Works and Water Resources, the Spatial Planning Agency, the Sub-district Office, and residents of Kayuringin Jaya Sub-district. Through thisiresearch, it is expected to reveal the roles of each stakeholder in the managementiof green open spaces in the Bekasi City Forest. The result of this study can provid a better understandin of the importance of stakeholder cooperation and participation in improving the effectiveness of green open space management. Issues were found within the Environmental Agency, indicating suboptimal performance due to inadequate communication analysis among stakeholders caused by existing SOPs within each agency. Theimanagement ofiithe Bekasi City Forestiihasiinot been fully implemented due to poor communication and lack of cooperation from non-governmental parties, thus failing to provide significant benefits to the community enjoying the area. Recommendations include the Environmental Agency improving communication among stakeholders involved in the management of the City Forest and fostering cooperation with non-governmental entities.